Notatki z Folger - Fish, Stanley (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The text written by Stanley Fish, which is an excerpt from his book Professional Correctness. Literary Studies and Political Change (Oxford 1995), is an attempt at a presentation and a discussion of the main conditioning factors and the aporia of interpretation. From among the four arguments given by the author, i.e. intention, historicalness, politicalness and interdisciplinarity, only the first one has been established to be an immanent feature of each of interpretations. This results from the conviction that while interpreting literary texts we are always subjected to the pressure of the surrounding premises. It is just the extensive and thorough analysis of these premises, to which the supporters of political, historical and interdisciplinary criticism refer to that makes the author of the sketch possible to show that behind each of the methods there are individual interests and a different vision of the world. To realize these determinants is to enable us to question the very need of universal interpretation. By questioning the theoretical fundamentals of the three mentioned modes of interpretation, the author admits frankly that the work of an interpreter can have both historical, political and just as well interdisciplinary character, though this observation is by all means tantamount to a recognition of the legitimacy of any of the criticized methods.